Adverse Event Of Epidermal Growth Factor Receptor (EGFR) Tyrosine Kinase Inhibitor (TKI) Treatment In Medan Among Pulmonary Adenocarcinoma: Focus On Non-Hematologic Toxicity - Putri Wulandari Harahap; Setia Putra Tarigan; Noni Novisari Soeroso (International Journal of Health and Pharmaceutical (IJHP), 2025)
This study aims to compare the non-hematological toxicities of first and second-generation Epidermal Growth Factor Receptor (EGFR) Tyrosine Kinase Inhibitors (TKIs) in pulmonary adenocarcinoma patients with positive EGFR mutations in Medan. Utilizing a retrospective cross-sectional design, data were collected from medical records of 66 patients at three hospitals between January 2017 and December 2022. The study population included all patients meeting the specific criteria, and a total sampling technique was used. The collected data on demographics and non-hematological side effects were analyzed using the SPSS program, with the Kolmogorov-Smirnov and chi-square tests. The results indicate that second-generation TKIs exhibit lower non-hematological toxicities, specifically for skin rash, stomatitis, and diarrhea, compared to first-generation TKIs. However, a significant association was found between second-generation TKIs and a higher incidence of paronychia. All observed side effects were low-grade. The study's limitations include its retrospective nature and focus on non-hematological toxicities. Future research should investigate the toxicity profiles of second-generation TKIs further, including hematological side effects.